Molecular pathology shows p16 methylation in nonadenomatous pituitaries from patients with Cushing's disease. - Simpson, D; McNicol, A; Murray, D; Bahar, A; Turner, H; Wass, J; Esiri, M; Clayton, R; Farrell, W (2004)
PURPOSE: The majority of cases of Cushing's disease are due to the presence of a corticotroph microadenoma. Less frequently no adenoma is found and histology shows either corticotroph hyperplasia, or apparently normal pituitary. In this study we have used molecular pathology to determine whether the tissue labeled histologically as "normal" is indeed abnormal. EXPERIMENTAL DESIGN: Tissue from 31 corticotroph adenomas and 16 nonadenomatous pituitaries were subject to methylation-sensitive PCR to determine the methylation status of the p16 gene CpG island. The proportion of methylated versus unmethylated CpG island was determined using combined bisulphite restriction analysis. Methylation status was correlated with immunohistochemical detection of p16. RESULTS: Seventeen of 31 adenomas (54.8%), 4 of 6 cases of corticotroph hyperplasia, and 7 of 10 apparently normal pituitaries showed p16 methylation. Ten of 14 (71%; P = 0.01) adenomas and 2 of 3 cases of corticotroph hyperplasia, which were methylated, failed to express p16 protein. However, only 2 of 7 apparently normal pituitaries that were methylated failed to express p16 protein. Quantitative analysis of methylation using combined bisulphite restriction analysis showed only unmethylated CpG islands in postmortem normal pituitaries; however, in adenomas 80-90% of the cells within a specimen were methylated. The reverse was true for corticotroph hyperplasia and apparently normal pituitaries where only 10-20% of the cells were methylated. Thus, the decreased proportion of cells that were methylated, particularly in those cases of apparently normal pituitary, is the most likely explanation for the lack of association between this change and loss of cognate protein in these cases. CONCLUSIONS: To our knowledge this is the first report that describes an intrinsic molecular change, namely methylation of the p16 gene CpG island, common to all three histological patterns associated with Cushing's disease. Thus, the use of molecular pathology reveals abnormalities undetected by routine pathological investigation. In cases of "apparently" normal pituitaries it is not possible to determine whether the change is associated with adenoma cells "scattered" throughout the gland, albeit few in number, or with the ancestor-clonal origin of these tumor cells.